2016
DOI: 10.1002/hep.28880
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of hepatitis C screening, characteristics of patients tested, and intervention costs in the BEST‐C study

Abstract: Background From December 2012-March 2014, three randomized trials, each implementing a unique intervention in primary care settings (mail recruitment [repeated-mailing], an electronic health record best practice alert [BPA], and patient-solicitation [patient-solicitation]), evaluated HCV antibody testing, diagnosis, and costs for each of the interventions compared to standard-of-care testing. Multilevel multivariable models were used to estimate the adjusted risk ratio (aRR) for receiving an HCV antibody test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
5
27
0
Order By: Relevance
“…Our finding of a screening rate, in response to the EMR reminder, of 37%, is within the range of HCV testing frequency reported in other studies with EMR‐based prompts, which have ranged from 30% to 88% . It should be noted that our centre did not initiate a specific training programme, making the implementation of this approach very simple.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our finding of a screening rate, in response to the EMR reminder, of 37%, is within the range of HCV testing frequency reported in other studies with EMR‐based prompts, which have ranged from 30% to 88% . It should be noted that our centre did not initiate a specific training programme, making the implementation of this approach very simple.…”
Section: Discussionsupporting
confidence: 81%
“…The seroprevalence of HCV among baby boomers undergoing EMR‐driven testing at our centre (1.6%) is comparable to the seroprevalence range (0.9%‐1.2%) reported by several urban healthcare centres that employed targeted HCV testing of the 1945‐1965 birth cohort, but lower than the 3.5% population estimate from NHANES . Several factors could account for this, including study population differences regarding race or ethnicity, birthplace, education, income, each of which is associated with differences in HCV seroprevalence, as well as differences in the NHANES era (1999‐2008) and the era in which targeted testing was performed (after 2013).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This degree of success likely depended, at least in part, on the staff and resources dedicated specifically to the trials. The trial that reported the highest testing rate did not integrate BC testing into the normal workflow but instead used a dedicated recruiter to perform direct patient invitation, an approach that may be less cost‐effective over a longer period . However, while the use of a recruiter dedicated to implementing a single health screening recommendation may represent a potentially prohibitive resource expense, population management (which often involves an assigned health professional working with patients) is increasingly being used in health systems to achieve population health goals .…”
Section: Discussionmentioning
confidence: 99%
“…1012 Analyses of national trends in hepatitis C testing have shown significant increases in testing among the birth cohort in the period following the recommendation change, 13,14 but the specific causal impact of this policy change on clinical practice has not been evaluated. Improvements in testing can lead to increased case finding, decreased hepatitis C transmission, and earlier initiation of antiviral treatment among infected persons, thus reducing morbidity and mortality related to hepatitis C. 1517 We analyzed hepatitis C screening rates in the United States in the period 2010–14, using a strong quasi-experimental design to determine the causal impact of the 2012 recommendation on rates of testing among people with commercial insurance in the birth cohort.…”
mentioning
confidence: 99%